"A Newcomer" versus "First Mover": Retail Location Strategy for Differentiation. Issue 1 (2nd January 2018) - Lee, Jinhyung; Kim, Youngho
Abstract : In a competitive business environment, retailers brand themselves using unique location strategies. New retailers, especially, use their location strategy to construct a different brand concept from that of the first mover. Therefore, retail chains in the same industry show different location patterns. This article aims to investigate how a new retailer uses its location strategy to differentiate itself from the first mover by comparing the location patterns of two coffee chains. The location patterns of Starbucks Coffee (a "first mover" that employs a premium brand concept) and Ediya Coffee (a "new retail chain" that promotes an economical brand concept) are analyzed for the study. We use a Bayesian spatial model to explore the two retailers' location patterns in Seoul, Korea. Considerable differences are found in the spatial distribution patterns of the two coffee franchises. Starbucks has formed store groupings in prime areas such as the city center based on its cluster location strategy, reflecting its premium brand concept. Conversely, many Ediya Coffee shops have been located in less desirable areas such as fringe areas with low land prices, reflecting their economical brand concept and differentiating the company from Starbucks. These findings lead to a useful marketing implication for a retail startup formulating its location strategy for differentiation. Furthermore, this study's company-level analysis of retail location patterns provides a better understanding of complex retail geography.